(untitled) (Revista de Física Médica, 2018)
The tomotherapy treatment unit has exclusive and specific modalities of intensity modulated radiotherapy (IMRT) owing to its design. The increasing implantation of these kind of devices, has motivated to resume the work, initiated in the framework of the task group on IMRT of the Medical Physics Spanish Society, to provide a set of recommended procedures for the quality assurance of IMRT in tomotherapy. The tests described in this document come mainly from those proposed by the manufacturer (later compiled in the report of the American Association of Medical Physics AAPM TG-148), others are based on publications of other users, and some have been contributed by the authors themselves. In any case, for each test, one or more methodologies (including the analysis) are described in detail, indicating the required equipment (preferably the one supplied with the treatment unit), the recommended periodicity and tolerance, as well as the time and minimum staff needed.